Comparative enrichment of complete ammonium oxidation bacteria in floccular sludge reactors: Sequencing batch reactor vs. continuous stirred tank reactor - Ying Zhu; Jiaying Hou; Fangang Meng; Meiying Xu; Limin Lin; Linyan Yang; Xueming Chen (Water Research X)
This study attempted to compare the enrichment of complete ammonium oxidation (comammox) bacteria, which are affiliated with Nitrospira and not able to generate nitrous oxide (N2O, a potent greenhouse gas) through biological pathways, in two commonly-utilized configurations of floccular sludge reactors, i.e., sequencing batch reactor (SBR) and continuous stirred tank reactor (CSTR), under the ammonium condition of mainstream wastewater (i.e., 40.0 g-N/m3). The results in terms of nitrification performance and microbial analyses during 216-d operation showed that compared with SBR offering a fluctuating but generally higher in-situ ammonium concentration (i.e., 1.0–6.0 g-N/m3) which was favorable for the growth of ammonium-oxidizing bacteria (AOB, belonging to Nitrosomonas in this study), CSTR managed to lower the in-situ ammonium level to < 2.0 g-N/m3, thus creating a competitive advantage for comammox bacteria with a highly oligotrophic lifestyle. Such an argument was further supported by dedicated batch tests which revealed that Nitrospira-dominant sludge had a lower maximum ammonium oxidation rate and lower apparent ammonium and oxygen affinity constants than Nitrosomonas-dominant sludge (i.e., 33.5 ± 2.1 mg-N/h/g-MLVSS vs. 139.9 ± 26.7 mg-N/h/g-MLVSS, 1.1 ± 0.1 g-N/m3 vs. 17.6 ± 4.6 g-N/m3, and 0.017 ± 0.002 g-O2/m3 vs. 0.037 ± 0.013 g-O2/m3, respectively), proving the nature of comammox bacteria as a K-strategist. Overall, this study not only provided useful insights into the effective enrichment of comammox bacteria in floccular sludge but also further revealed the interactions between comammox bacteria and AOB, thereby contributing to the future development of comammox-inclusive biological nitrogen removal technologies for sustainable wastewater treatment.